A emergência da lateral pós-vocálica em inglês-L2 de falantes do português brasileiro - Jamila Viegas Rodrigues (2014)
This dissertation examines the emergence of the post-vocalic lateral in English-L2 speakers of Brazilian Portuguese (BP). Considering that the post-vocalic lateral does not occur in BP-L1, its occurrence in L2 involves the emergence of this category. We intend to evaluate the pathways of the emergence of post-vocalic lateral in English-L2 through the study with 12 BP speakers from Belo Horizonte, Minas Gerais, and thus contribute to expanding the regional knowledge about English-L2 of Brazilian speakers. We adopt as theoretical approach the Complex Adaptive Systems (ALBANO, 2012; BYBEE, 2001, 2010; ELLIS, ROBINSON, 2008 LARSEN-FREEMAN, 1997). We believe that the theoretical discussion of the new models can contribute to a greater understanding of the English-L2 phonology of Brazilian Portuguese speakers. Two British English native speakers were recorded for a control group. A collaborator, Persian native speaker, collaborated on the examination of data along with the author of this dissertation. The first step of data collection was the application of the Vocabulary Levels Test (VLT) to confirm the participants' level of proficiency. Soon after, participants began the experiment recording session. The categorical analysis followed a hearing assessment and was based on the evaluation of spectrograms to classify each given segment as a post-vocalic lateral or as a posterior glide. The statistical analysis included the significance test by calculating the Chi-square and Cramer's V. The results indicated that the time of exposure to L2 and the individual are statistically significant factors for the emergence of the post-vocalic lateral in Brazilian English-L2 speakers. On the other hand, the lexical item, the lateral position in the word and in word juncture did not show statistically significant results and were not included as relevant to the emergence of post-vocalic lateral. The results are consistent with the perspective that suggests that segmental emergency, and more specifically the post-vocalic lateral emergence in English-L2, reflects the dynamic and complex self-organization of the learner phonological system over time and with the specificities of individual in the construction of grammatical knowledge.